Mass customization in practice - Patalas-Maliszewska, J. (Advances in production engineering and management, 2025)
Implementing a mass customization (MC) strategy in manufacturing enterprises presents an ongoing challenge for both managers and researchers. To remain competitive, managers must consider adopting advanced technologies associated with Industry 4.0 and 5.0 (I4.0/5.0). This study seeks to identify solutions that support strategic decision-making aimed at enhancing the level of MC implementation. The paper begins with a literature review focused on the adoption of MC strategies within European manufacturing enterprises. It then presents findings from a questionnaire-based survey conducted among more than 100 small and medium-sized enterprises (SMEs) in Poland’s automotive sector. Statistical analysis, including correlation coefficients, was used to evaluate the data. The results indicate that consumer participation in the product design process is the key driver of successful MC strategy implementation in the surveyed SMEs. Furthermore, managers recognized strong correlations between the adoption of I4.0/5.0 technologies—such as automated machinery and real-time data usage—and higher levels of MC capability. The benefits of implementing MC strategies, including increased production flexibility and waste reduction, were also highlighted. The findings offer general insights applicable to SMEs in the automotive industry.
Keywords: automotive industry; avtomobilska industrija; consumer participation; Industrija 4.0; Industry 4.0/5.0 technologies; Industry 5.0; mass customisation strategy; medium sized manufacturing enterprises; prilagodljiva proizvodnja; production flexibility; proizvodna strategija; small sized manufacturing enterprises; strategija prilagajanja strankam